Relationship between parental participation and adolescents’ academic success in Nadia and Jalpaiguri districts - Mondal, Mallika; Panda, Bijoy Krishna; Sinha, Muktipada (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2023)
The present study investigated the relationship between parents’ participation in their children’s education and academic success in the post-pandemic period. A cross-sectional survey design was used, and 209 respondents were selected through a simple random sampling technique. The results revealed that parental involvement has a negative correlation (p>0.05) with their children’s academic success but not significantly affecting the same. Apart from that, some other social and educational attributes of the children also contributed to their academic success to a great extent. Further research is needed to explore other potential factors that may contribute to academic success in children.